2018
DOI: 10.1002/mma.5402
|View full text |Cite
|
Sign up to set email alerts
|

Evolutes of fronts in the Minkowski plane

Abstract: We consider the differential geometry of evolutes of singular curves and give the definitions of spacelike fronts and timelike fronts in the Minkowski plane. We also give the notions of moving frames along the non‐lightlike fronts in the Minkowski plane. By using the moving frames, we define the evolutes of non‐lightlike fronts and investigate the geometric properties of these evolutes. We obtain that the evolute of a spacelike front is a timelike front and the evolute of a timelike front is a spacelike front.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 8 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…From ( 4), it follows T ⊥sp {N, B 2 }. Then, multiplying (9) with N and B 2 , we have l(s) = 0, n(s) = 0, respectively, and (9) becomes T (s) = p(s)T (s) + r(s)B 1 (s), (10) and from (10), it follows p 2 (s) + r 2 (s) = 1, since T is unit. Differentiating (10) with respect to s and using Frenet formulas (1), we get…”
Section: (13)-bertrand-direction Curves In Ementioning
confidence: 99%
See 1 more Smart Citation
“…From ( 4), it follows T ⊥sp {N, B 2 }. Then, multiplying (9) with N and B 2 , we have l(s) = 0, n(s) = 0, respectively, and (9) becomes T (s) = p(s)T (s) + r(s)B 1 (s), (10) and from (10), it follows p 2 (s) + r 2 (s) = 1, since T is unit. Differentiating (10) with respect to s and using Frenet formulas (1), we get…”
Section: (13)-bertrand-direction Curves In Ementioning
confidence: 99%
“…Özyılmaz and Yılmaz studied involute-evolute of W -curves in Euclidean 4-space E 4 [16]. Li and Sun studied evolutes of fronts in the Minkowski Plane [9].…”
Section: Introductionmentioning
confidence: 99%
“…This theory is also used to link physics and mathematics. Many other sub-disciplines of mathematics, including differential geometry and algebra, utilize from it (Li and Sun 2019). The idea of combining differential geometry with singularity theory was proposed by Arnold (1990) and Thom (1956).…”
Section: Introductionmentioning
confidence: 99%
“…Some new results concerning the singularities of submanifolds were established by the second author and his collaborators. [12][13][14][15][16][17][18][19][20][21][22][23][24] As an application of singularity theory, in this paper, we study the singularities of the Darboux developable of nth principal-directional curve of a curve. It is demonstrated that the ratio of torsion to curvature of a curve play a key role in characterizing the singularities of the Darboux developables of the nth principal-directional curve of a curve .…”
Section: Introductionmentioning
confidence: 99%
“…Better understanding of the local topological structure of singularities of a manifold is very important. Some new results concerning the singularities of submanifolds were established by the second author and his collaborators 12‐24 . As an application of singularity theory, in this paper, we study the singularities of the Darboux developable of n th principal‐directional curve of a curve.…”
Section: Introductionmentioning
confidence: 99%